Instantaneous fluctuation velocity and skewness distributions upstream of transition onset - Hernon, D; Walsh, E; McEligot, D (2007)
The development of streamwise orientated disturbances through the boundary layer thickness prior to transition onset for zero-pressure gradient boundary layer flow under the influence %Tu = 4.2 is presented. The analysis concentrates on the development of the maximum positive and negative of the fluctuation velocity in order to gain further insight into the transition process. The average location of the peak negative fluctuation velocity over a range of Reynolds numbers was measured in the upper portion of the boundary layer at y/δ ≈ 0.6, whereas the location of the peak positive value was measured at y/δ ≈ 0.3. The disturbance magnitude of the negative fluctuation velocity increased beyond that of the positive as transition onset approached. The distribution and disturbance magnitude of the maximum positive and negative fluctuation velocities indicate that the initiation of transition may occur on the low-speed components of the flow that are lifted up to the upper region of the boundary layer. This is in qualitative agreement with recent direct numerical simulations on the breakdown of the flow on the lifted low-speed streaks near the boundary layer edge. The results presented in this investigation also demonstrate the increased physical insight gained by examining the distributions of the maximum positive and negative of the streamwise fluctuation velocity component associated with the low- and high-speed streaks, compared to time-averaged values, in determining what structures cause the breakdown to turbulence. © 2007 Elsevier Inc. All rights reserved.